Association Between Antibiotic Treatment of Chlamydia pneumoniae and Reduced Risk of Alzheimer Dementia: A Nationwide Cohort Study in Taiwan - Ou, Hsun; Chien, Wu-Chien; Chung, Chi-Hsiang; Chang, Hsin-An; Kao, Yu-Chen; Wu, Pei-Chuan; Tzeng, Nian-Sheng (Frontiers in Aging Neuroscience, 2021)
Background:Chlamydia pneumoniae (CPn) is a common community-acquired pneumonia. In the literature, CPn infection is demonstrated to exhibit an association with Alzheimer dementia (AD). We executed the present nationwide, population-based research with the goal of probing the association of CPn infection and antibiotic therapy with AD risk. Methods: We conducted a cohort study using a database extracted from Taiwan's National Health Insurance Research Database (NHIRD). All medical conditions for each enrolled individuals were categorized using the International Classification of Diseases, ninth Revision classifications. Hazard ratios (HRs) and 95% confidence intervals (CIs) for associations between CPn pneumonia-associated hospitalizations and AD were estimated using Fine and Gray's survival analysis and adjusted for comorbidities. The effects of the antibiotics on the HRs for AD in the patients with CPn pneumonia-associated hospitalization were also analyzed. Results: Our analyses included 6,628 individuals, including 1,657 CPn-infected patients, as well as 4,971 controls matched by age, index date, and sex (1:3). In this study, patients hospitalized for CPn pneumonia exhibited a significantly higher AD risk (adjusted HR = 1.599, 95% CI = 1.284–1.971, p < 0.001). We also noted an association of macrolide use (≥15 days) and fluoroquinolone use (≥15 days) with decreased AD risk. Conclusions: We determined CPn pneumonia to be associated with a relatively high AD risk. The result in this study confirmed the findings from previous literatures, by using a large, nationwide, population-based database. Appropriate macrolide and fluoroquinolone treatment may attenuate this risk.